ASSIGNMENTS FOR TEACHINGINTERCULTURAL COMMUNICATION - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
The article discusses the indicative tasks for the formation of socio-cultural competence in the process of teaching students of language specialties to intercultural communication. The tasks are aimed at mastering students’ knowledge of the ethnopsychological peculiarities of the native speaker of the studied language and the ability to use this knowledge in the process of interaction. The complex is based on methodological principles of interrelated communicative and socio-cultural development of the student’s personality, the gradual formation of socio-cultural competence and the comparison of native and foreign cultures. Examples of socio-cultural tasks based on the material of the English language are given.